La preparación al matrimonio según la Exhortación Apostólica Familiaris Consortio . Una reflexión sobre el documento en el 30 aniversario de su elaboración - Robert Kantor (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Marriage is an important event in the life of engaged couple as well as the whole community of believers. The preparation for marriage requires that the couple should be introduced into the Catholic ecclesial teaching about the rights and duties which result from contracted marriage. The article presents the issue of preparation for marriage; the stages according to the Apostolic Exhortation Familiaris Consortio . The study includes the following issues: the preparation stage; the need of preparation to marriage; stages and content of the preparation; people responsible for the preparation; permission to celebrate marriage of baptized individuals who are not suf fi ciently prepared.